Surgical Resection of Thymoma Still Represents the First Choice of Treatment - Ried, M.; Guth, H.; Potzger, T.; Diez, C.; Neu, R.; Schalke, B.; Hofmann, H.-S. (The Thoracic and Cardiovascular Surgeon, 2012)
Objective The aim of this study was to analyze the clinicopathological factors, treatment strategies and survival rates after surgical resection of thymoma.Methods Between 12/1997 and 5/2010, 42 patients underwent surgical resection of the thymus. The presence of a thymoma was determined by histological examination in 23 patients, while patients with hyperplasia of the thymus (n = 19) were excluded from further analysis.Results Myasthenia gravis coexisted in 9/23 (39.1%) patients. Thymomas were classified according to the Masaoka staging system (I: n = 6 [26.1%], IIa: n = 7 [30.4%], IIb: n = 2 [8.7%], III: n = 1 [4.4%], IVa: n = 7 [30.4%]) and the WHO histological classification (A: n = 4 [17.4%], AB: n = 5 [21.7%], B1: n = 1 [4.4%], B2: n = 8 [34.8%], B3: n = 3 [13%], C: n = 2 [8.7%]). Recurrence of thymoma was documented in three (13%) patients. After a mean follow-up of 58.4 months, 21 (91.3%) patients are alive. The overall survival rate was 95% and 87.8%, at 2 and 5 years, respectively. The disease-free interval at 5 years was 85% for the 17 (73.9%) patients with complete resection.Conclusions Surgical resection of thymoma is the preferred treatment, because it is safe and effective with a low rate of recurrence and a good long-term survival. Advanced and invasive thymomas require a multimodal approach for better local tumor control and further improvement of prognosis.
Keywords: thymoma; thymic carcinoma; thymus hyperplasia; myasthenia gravis